High paracrine activity of hADSCs cartilage microtissues inhibits extracellular matrix degradation and promotes cartilage regeneration - Wei Liu; Hongyu Jiang; Jiajie Chen; Yue Tian; Ying He; Ying Jiao; Yanjun Guan; Zhibo Jia; Yanbin Wu; Cheng Huang; Yiben Ouyang; Wenjing Xu; et al. (Materials Today Bio)
Due to its unique structure, articular cartilage has limited self-repair capacity. Microtissues are tiny tissue clusters that can mimic the function of target organs or tissues. Using cells alone for microtissue construction often results in the formation of necrotic cores. However, the extracellular matrix (ECM) of native cartilage can provide structural support and is an ideal source of microcarriers. Autologous adipose-derived mesenchymal stem cells (ADSCs) and bone marrow mesenchymal stem cells (BMSCs) are widely used in cartilage tissue engineering. In this study, we fabricated microcarriers and compared the behavior of two homologous cell types in the microcarrier environment. The microcarrier environment highlighted the advantages of ADSCs and promoted the proliferation and migration of these cells. Then, ADSCs microtissues (ADSCs-MT) and BMSCs microtissues (BMSCs-MT) were fabricated using a three-dimensional dynamic culture system. In vitro and in vivo experiments verified that the cartilage regeneration ability of ADSCs-MT was significantly superior to that of BMSCs-MT. Transcriptomics revealed that ADSCs-MT showed significantly lower expression levels of ECM degradation, osteogenesis, and fibrocartilage markers. Finally, the protective effect of microtissues on inflammatory chondrocytes was validated. Overall, the ADSCs-MT constructed in this study achieved excellent cartilage regeneration and could be promising for the autologous application of cartilage microtissues.